Influence of Service Quality and Owner's Personal Branding on Decisions to Use Training Services Through Customer Trust - R. Rianik; Ike Kusdyah Rachmawati; Yunus Handoko (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of service quality and the owner's personal branding on customers' decision to use training services, through customer trust, at PT Kemilau Cahaya Inspirasi, Sidoarjo. The study used primary data collected through questionnaires distributed to training participants who had attended training more than once during the period from January 2023 to September 2025, with a sample of 80 respondents. The sampling technique was non-probability purposive sampling. The data were analyzed quantitatively using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that service quality and the owner's personal branding have a positive and significant effect on customer trust; however, they do not directly affect the decision to use training services. Customer trust significantly affects the decision to use training services and serves as a mediating variable. The main finding of this study shows that customer trust is a key factor that bridges the influence of service quality and personal branding on customers' decisions to use training services. Accordingly, trust plays a strategic role in strengthening the decision to use training services.